6a-2-4a=3a+4+5a

Simple and best practice solution for 6a-2-4a=3a+4+5a equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6a-2-4a=3a+4+5a equation:


Simplifying
6a + -2 + -4a = 3a + 4 + 5a

Reorder the terms:
-2 + 6a + -4a = 3a + 4 + 5a

Combine like terms: 6a + -4a = 2a
-2 + 2a = 3a + 4 + 5a

Reorder the terms:
-2 + 2a = 4 + 3a + 5a

Combine like terms: 3a + 5a = 8a
-2 + 2a = 4 + 8a

Solving
-2 + 2a = 4 + 8a

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-8a' to each side of the equation.
-2 + 2a + -8a = 4 + 8a + -8a

Combine like terms: 2a + -8a = -6a
-2 + -6a = 4 + 8a + -8a

Combine like terms: 8a + -8a = 0
-2 + -6a = 4 + 0
-2 + -6a = 4

Add '2' to each side of the equation.
-2 + 2 + -6a = 4 + 2

Combine like terms: -2 + 2 = 0
0 + -6a = 4 + 2
-6a = 4 + 2

Combine like terms: 4 + 2 = 6
-6a = 6

Divide each side by '-6'.
a = -1

Simplifying
a = -1

See similar equations:

| 0=-5n-2n-2n | | (-5)=b+(-11) | | -8x^2-8x+160=0 | | A-5=(-8) | | 3x*26= | | 6(x-1)+2=6x-2 | | -7y=-10-8y | | 0=-4.9t^2+.686t | | J+(-3)=4 | | 7j+4=5j | | -5x-15=-20 | | 9y=9+10y | | -12+8+5=36 | | 2x+34x^2-322=0 | | 3+(-7)=f-3 | | 3y+9-8y+6-6=-5y-12 | | -12+3x=-6 | | 9n=-117 | | 3x+9-8x+6-6=-5x-12 | | 3+(-7)=4 | | -0.9+z=0.075 | | 69=3u | | 0.06x+0.02(7-x)= | | 6p+4= | | 8-3=3x-2-8x | | 4+e=8+(-2) | | 3(5x+3)=6x-3+5x+3 | | 10b+50=30 | | 10x^2+13x+-9=0 | | -(x+5)=-1 | | 5h-12=4h+6 | | 3(-4+3)=2 |

Equations solver categories